PRESENTATIONS OF TUBERCULOSIS IN NORTHERN PAKISTAN - Tariq, Sumbal; Rauf, Abdul; Malik, Saqib; Rashid, Abdul (Journal of Ayub Medical College Abbottabad, 2011)
Background: Tuberculosis (TB), which is a very common droplet infection. If untreated, the disease may be fatal within 5 years in more than half of cases. The aim of this hospital based descriptive study was to see mode of its presentation in our set-up. Method: The study was conducted in Medical Unit, Ayub Teaching Hospital, Abbottabad and 500 diagnosed cases of tuberculosis were included in this study. History regarding presenting symptoms, age, sex, etc. was taken. Results: Out of the 500 patients, 277 (55.4%) were male and 223 (44.6%) were female. Two-hundred-three (40.5%) were in age group 21-35 years, 136 (27.1%) were in age group 36-50 years, 141 (28.1%) were in age group 51-65 years while 20 (4%) were above 65 years of age. Three-hundred-and-eighty (76%) presented as Pulmonary TB, 47 (9.4%) as Abdominal TB, 45 (9%) as TB Meningitis, 13 (2.6%) as Pott’s Disease, 7 (1.4%) as TB Lymphadenitis, 6 (1.2%) as Constrictive Pericarditis, 1 (0.2%) as Psoas Abscess and 1 (0.2%) as TB Orchitis. Conclusion: TB in its various forms remains a killer disease in our part of the world. The commonest presentation is Pulmonary TB which is probably due to three major factors namely poor hygienic practices, late diagnosis and non-compliance. Keywords: Tuberculosis, Acid Fast Bacillus, Pott’s disease, Psoas Abscess, Non-Compliance